Efficacy and Safety of Tripterygium Wilfordii Hook. F for Connective Tissue Disease-Associated Interstitial Lung Disease:A Systematic Review and Meta-Analysis - Li, Yehui; Zhu, Wen; He, Hailang; Garov, Yordan Angelov; Bai, Le; Zhang, Li; Wang, Jing; Wang, Jinghai; Zhou, Xianmei (Frontiers in Pharmacology, 2021)
Background: Tripterygium wilfordii Hook. F (TwHF), a Chinese herbal medicine used to treat CTD-ILD patients in China, has been previously found to have immunoinhibitory, antifibrotic and anti inflammatory effects. It has also shown good results in treating autoimmune and inflammatory diseases. Objectives: This systematic review and meta-analysis aims to evaluate the efficacy and safety of TwHF for CTD-ILD. Methods: A systematic search was performed on PubMed, Embase, Cochrane Library, Web of Science, PsycINFO, Scopus, CNKI, Wanfang, VIP, and CBM databases up to May 2021. Randomized controlled trials (RCTs) comparing TwHF plus conventional therapy versus conventional therapy alone were included. We followed the PRISMA checklist, and applied Cochrane handbook 5.1.0 and RevMan 5.3 for data analysis and quality evaluation of the included studies. Results: Based on Cochrane handbook 5.1.0, nine RCTs consisting 650 patients met the inclusion/exclusion criteria and were selected for further analysis. The obtained data showed significant improvement in lung function with TwHF plus conventional treatment compared with conventional treatment (post-treatment FVC% (MD= 8.68, 95%Cl (5.10, 12.26), p < 0.00001), FEV1% (MD = 11.24, 95%Cl (6.87, 15.61), p < 0.00001), TLC% (MD = 5.28, 95%Cl (0.69, 9.87), p = 0.02)], but no significant difference in the post-treatment DLCO% [(MD = 4.40, 95%Cl (−2.29, 11.09), p = 0.20)]. Moreover, the data showed that TwHF combined with conventional treatment significantly reduced the HRCT integral of patients [MD = -0.65, 95% (-1.01, -0.30), p = 0.0003], the level of erythrocyte sedimentation rate (MD = −9.52, 95%Cl (−11.55, −7.49), p < 0.00001), c-reactive protein (CRP) (MD = −8.42, 95%Cl (−12.47, −4.38), p < 0.0001), and rheumatoid factor (MD = −25.48, 95%Cl (−29.36, −21.60), p < 0.00001). Compared to conventional therapy, TwHF combined with conventional therapy significantly improved clinical effects (RR = 1.33, 95%Cl (1.17, 1.51), p < 0.0001), in five trials with 354 patients. In terms of improvement of symptoms and signs, the TwHF group showed a more significant improvement than the conventional treatment group (Cough (MD = −0.96, 95%Cl (−1.43, −0.50), p < 0.0001), velcro rales (MD = −0.32, 95%Cl (−0.44, −0.20), p < 0.00001), shortness of breath (MD = −1.11, 95%Cl (−1.67, −0.56), p < 0.0001)], but no statistical difference in dyspnea (MD = −0.66, 95%Cl (−1.35, 0.03), p = 0.06). There was no statistical significance in the incidence of adverse reactions. Conclusion: The performed meta-analysis indicated that TwHF combined with conventional treatment was more beneficial to patients for improving symptoms, lung function and laboratory indicators. As it included studies with relatively small sample size, the findings require confirmation by further rigorously well-designed RCTs.